Entrepreneurship programmes should invest in alumni networks / Priestly Lanting Layang... [et al.] - Layang, Priestly Lanting; Abang Shamsudin, Dayang Nurul Amieyda; Herman, Nurul Izzah; Standard, Stephanie Sonia; Mokhtar, Muhammad Adib Azfar (Perpustakaan Tun Abdul Razak, 2023)
What happens after entrepreneurs complete a three-to-ninemonth accelerator programme, which frequently includes months of training, pitch presentations, and graduation? Many corporate funders and programme managers are left with this question. Without an answer, it is nearly impossible to measure and report the medium- and long-term effects of a programme. It is difficult to argue for increased funding, implement improvements, enhance sustainability reporting, and strengthen broader entrepreneurship ecosystems in the absence of impact data. What happens after entrepreneurs complete a three-to-ninemonth accelerator programme, which frequently includes months of training, pitch presentations, and graduation? Many corporate funders and programme managers are left with this question. Without an answer, it is nearly impossible to measure and report the medium- and long term effects of a programme. It is difficult to argue for increased funding, implement improvements, enhance sustainability reporting, and strengthen broader entrepreneurship ecosystems in the absence of impact data.